Efficacy of Neuroendoscopic Treatment for Septated Chronic Subdural Hematoma - Deng, Jianhong; Wang, Fangyu; Wang, Haojie; Zhao, Mingpei; Chen, Guorong; Shangguan, Huangcheng; Yu, Lianghong; Jiang, Changzhen; Fang, Wenhua; Yao, Peisen; Kang, Dezhi; Zheng, Shufa (Frontiers in Neurology, 2022)
Objective Neuroendoscopic treatment is a potential therapeutic alternative to septated chronic subdural hematoma (sCSDH). However, the safety and efficacy of neuroendoscopic treatment remains controversial. Herein, we summarized the clinical data of neuroendoscopic treatment and standard (large bone flaps) craniotomy for sCSDH in our single center, and further evaluated the safety and efficacy of neuroendoscopic treatment for sCSDH. Methods The clinical data of 43 patients with sCSDH underwent neuroendoscopic treatment or standard (large bone flaps) craniotomy, including sex, age, smoking, drink, medical history, taking antiplatelet drugs or not, postoperative complication, sCSDH recurrence or not, length of hospital stay and postoperative hospital stay were retrospectively collected. The surgical procedures and neurological function recovery before operation and 6 months after surgical treatment were recorded. Results Forty-three patients (37 men and 6 women) with sCSDH were enrolled. The neuroendoscopic treatment group and standard (large bone flaps) craniotomy group had 23 and 20 patients respectively. There were no differences in sex, age, smoking, drink, medical history, taking antiplatelet drugs or not, postoperative complication and sCSDH recurrence or not between the two groups (p>0.05). However, the patients in neuroendoscopic treatment group had a shorter length of total hospital stay and postoperative hospital stay than standard craniotomy group（length of total hospital stay:5.26±1.89 vs 8.15±1.04 days，p<0.001；length of postoperative hospital stay：4.47±1.95 vs 7.96±0.97 days，p<0.001）. The imaging and mRS at 6-months follow-up were satisfactory, and no sCSDH recurrence between the two groups was found. Conclusions Neuroendoscopic evacuation was an effective and safe treatment for sCSDH, which was minimally invasive, and worthy of clinical promotion.